2008
DOI: 10.1529/biophysj.108.132563
|View full text |Cite
|
Sign up to set email alerts
|

Four-Scale Description of Membrane Sculpting by BAR Domains

Abstract: BAR domains are proteins that sense and sculpt curved membranes in cells, furnishing a relatively well-studied example of mechanisms employed in cellular morphogenesis. We report a computational study of membrane bending by BAR domains at four levels of resolution, described by 1), all-atom molecular dynamics; 2), residue-based coarse-graining (resolving single amino acids and lipid molecules); 3), shape-based coarse-graining (resolving overall protein and membrane shapes); and 4), a continuum elastic membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
329
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(335 citation statements)
references
References 78 publications
6
329
0
Order By: Relevance
“…The same idea (in a slightly different implementation) has recently been applied by Arkhipov et al to a different solvent free CG lipid model. 212 These authors also find that within the obtained accuracy the measured bending modulus does not depend on tether radius.…”
Section: Example Applicationsmentioning
confidence: 57%
“…The same idea (in a slightly different implementation) has recently been applied by Arkhipov et al to a different solvent free CG lipid model. 212 These authors also find that within the obtained accuracy the measured bending modulus does not depend on tether radius.…”
Section: Example Applicationsmentioning
confidence: 57%
“…These theories showed that two undeformable parallel rods undergo an attractive interaction, but the interaction is repulsive for a perpendicular orientation. The adsorption and assembly of BAR domains have been investigated using atomic and coarse-grained molecular simulations [48][49][50]. Further, tubular formation via membrane protrusion was simulated using a dynamically triangulated membrane model [51,52] and meshless membrane models [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Atomic and coarse-grained molecular simulations [40][41][42][43][44][45] have been employed to investigate molecular-scale interactions between BAR proteins and lipids. The scaffold formation [43] and linear assembly [44] of BAR domains have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%